Response of ammonia-oxidizing bacteria and archaea to biochemical quality of organic inputs combined with mineral nitrogen fertilizer in an arable soil - Muema, E.K.; Cadisch, Georg; Rohl, C.; Vanlauwe, Bernard; Rasche, F. (Elsevier, 2015)
There exists a considerable knowledge gap about the effect of biochemical quality of organic inputs and their combination with inorganic N on abundance and community composition of ammonia-oxidizing archaea (AOA) and bacteria (AOB). Here, we investigated in a Humic Nitisol of 10-year old field experiment in Kenya the effect of contrasting organic inputs (i.e., Tithonia diversifolia (TD; C/N ratio: 13, Lignin: 8.9%; Polyphenols: 1.7%), Calliandra calothyrsus (CC; 13; 13; 9.4) and Zea mays (ZM; 59; 5.4; 1.2); rate of 4 Mg C ha−1 year−1) combined with mineral N fertilizer (120 kg CaNH4NO3 ha−1 growing season−1) on amoA gene-based abundance (i.e., functional potential) and community composition of AOB and AOA. AOB abundance was significantly lower in CC and ZM compared to TD, whereas AOA abundance was significantly lower in CC compared to ZM and TD. This reduction was attributed to a considerable N stress induced by limited organic N availability in ZM and polyphenol-protein complexes in CC. High abundance of AOA under ZM was attributed to their affinity to ammonium under N limiting conditions. Abundance shifts matched observed community composition differences between TD versus ZM (AOB) as well as TD versus ZM and CC (AOA). Mineral N irrespective of organic input type depressed abundance of AOA, but not AOB. This implied utilization of ammonium from fertilizer and organic N by AOB, while AOA mainly utilized ammonium from organic N. Our findings suggested input type dependent effects on AOB/AOA abundance and community composition, but influence of other factors such as soil type, seasonality and crop growth stages remain uncertain. These factors should not only be studied on basis of the functional potential of ammonia oxidizing prokaryotes as given in this study, but also by rRNA analyses to capture the active proportion of existent AOB and AOA.